Effects of Price, Brand, and Store Information on Buyers’ Product Evaluations - Dodds, William B.; Monroe, Kent B.; Grewal, Dhruv (Journal of Marketing Research, 1991)
The authors report a study of the effects of price, brand, and store information on buyers’ perceptions of product quality and value, as well as their willingness to buy. Hypotheses are derived from a conceptual model positing the effects of extrinsic cues (price, brand name, and store name) on buyers’ perceptions and purchase intentions. Moreover, the design of the experiment allows additional analyses on the relative differential effects of price, brand name, and store name on the three dependent variables. Results indicate that price had a positive effect on perceived quality, but a negative effect on perceived value and willingness to buy. Favorable brand and store information positively influenced perceptions of quality and value, and subjects’ willingness to buy. The major findings are discussed and directions for future research are suggested.